2002
DOI: 10.1046/j.1365-2036.2002.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent control of intragastric pH by pantoprazole, 10, 20 or 40 mg, in healthy volunteers

Abstract: Background: Proton pump inhibitors have emerged as the most effective class of drugs for the treatment of gastro‐oesophageal reflux. Pantoprazole is a proton pump inhibitor that has demonstrated high clinical efficacy. Aim: To evaluate the effect of once‐daily doses of pantoprazole, 10, 20 and 40 mg, on gastric acidity in healthy volunteers. Methods: Thirty‐six subjects received pantoprazole in a three‐way crossover design study. Ambulatory 24‐h intragastric pH and distal oesophageal pH were monitored at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
2
16
1
Order By: Relevance
“…Tutuian et al demonstrated that pantoprazole 40 mg once daily provides a linear, dose-dependent suppression of gastric acidity, with a median intragastric pH of 4.02 in 24 hours. 25 A recent study by Somberg et al showed that pantoprazole provides a mean gastric pH of 4.43 in intensive care unit patients in 24 hours. 26 We included patients in the early phase after HTx, but also patients in the late phase of HTx in order to minimize the limitations of the different therapeutic regimens.…”
Section: Discussionmentioning
confidence: 98%
“…Tutuian et al demonstrated that pantoprazole 40 mg once daily provides a linear, dose-dependent suppression of gastric acidity, with a median intragastric pH of 4.02 in 24 hours. 25 A recent study by Somberg et al showed that pantoprazole provides a mean gastric pH of 4.43 in intensive care unit patients in 24 hours. 26 We included patients in the early phase after HTx, but also patients in the late phase of HTx in order to minimize the limitations of the different therapeutic regimens.…”
Section: Discussionmentioning
confidence: 98%
“…This volume was chosen based upon the study by the Zurich group [8] and on preliminary experiments with other doses (data not shown). A pH value of 2.0 was used to reflect physiological value for GJ [23]. We preferred GJ instead of HCl/pepsin mixture as it is thought that bile acids and pepsin may also play a role in inducing airway inflammation [24].…”
Section: Discussionmentioning
confidence: 99%
“…15 Therefore, PPIs have emerged as the most effective class of drugs for the treatment of gastroesophageal reflux disease, as well as several other acid-related disorders. 16 All PPIs inhibit gastric acid secretion through binding with H ϩ /K ϩ -adenosine triphosphatase in gastric parietal cells and thereby they can modify the intragastric release of other drugs by elevating the pH value. For pantoprazole, lansoprazole and omeprazole, this binding is irreversible, whereas rabeprazole exhibits reversible binding to the proton pump.…”
mentioning
confidence: 99%